Analisis Faktor yang Mempengaruhi Profitabilitas Lembaga Perkreditan Desa - Utami, Ni Wayan Sari; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 34 No 3 (2024)DO - 10.24843/EJA.2024.v34.i03.p15, 2024)
The research aims to determine the effect of savings, capital adequacy and credit distribution on profitability with non-performing loans as a moderating variable. Saturated sampling technique was used in this research so that all members of the population were used as research samples, namely 33 Village Credit Institutions (LPD) in Sukawati District. This research uses the Moderated Regression Analysis (MRA) analysis technique, with the data used coming from the annual financial reports of LPDs in Sukawati District from 2017 to 2021. The results of this research show that savings, capital adequacy and credit distribution partially have a positive effect on profitability LPD. Non-performing loans have a negative effect on LPD profitability. In addition, non-performing loans partially weaken the influence of savings and credit distribution on LPD profitability. Non-performing loans strengthen the influence of capital adequacy on LPD profitability. Keywords: Savings; Capital Adequacy; Lending; Non-Performing Loan; Profitability